Comparative study of antibacterial properties of polystyrene films with TiO x and Cu nanoparticles fabricated using cluster beam technique - Popok, Vladimir N; Jeppesen, Cesarino M; Fojan, Peter; Kuzminova, Anna; Hanuš, Jan; Kylián, Ondřej (Beilstein journal of nanotechnology, 2018)
Background: Antibacterial materials are of high importance for medicine, and for the production and conservation of food. Among these materials, polymer films with metal nanoparticles (NPs) are of considerable interest for many practical applications. Results: The paper describes a novel approach for the formation of bactericidal polymer thin films (polystyrene in this case), produced by spin-coating, with Ti and Cu NPs deposited from cluster beams. Ti NPs are treated in three different ways in order to study different approaches for oxidation and, thus, efficiency in formation of the particles with semiconducting properties required for the catalytic formation of reactive oxygen species. Cu NPs are used as deposited. Partial NP embedding into polystyrene is realised in a controllable manner using thermal annealing in order to improve surface adhesion and make the particles resistant against wash-out. The formed composite films with TiO x and Cu species are tested as bactericidal media using E.coli bacteria as model microorganisms. Conclusion: The obtained results show considerable efficiency in destroying the bacteria and a good possibility of multiple re-use of the same composite films making the suggested approach attractive for the cases requiring reusable polymer-based antibacterial media.
Keywords: cluster beam technique; antibacterial properties; nanoparticles; polymers